2009
DOI: 10.1016/j.bbagrm.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

RNA conformational changes in the life cycles of RNA viruses, viroids, and virus-associated RNAs

Abstract: The rugged nature of the RNA structural free energy landscape allows cellular RNAs to respond to environmental conditions or fluctuating levels of effector molecules by undergoing dynamic conformational changes that switch on or off activities such as catalysis, transcription or translation. Infectious RNAs must also temporally control incompatible activities and rapidly complete their life cycle before being targeted by cellular defenses. Viral genomic RNAs must switch between translation and replication, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 148 publications
(204 reference statements)
1
46
0
Order By: Relevance
“…13,27,[30][31][32][33][34] These observations highlight the crucial role of complex tertiary interactions that span thousands of nucleotides in viral genomes (reviewed in ref. [35][36][37].…”
Section: Dynamic Rna Structures In the Dengue Virus Genomementioning
confidence: 99%
“…13,27,[30][31][32][33][34] These observations highlight the crucial role of complex tertiary interactions that span thousands of nucleotides in viral genomes (reviewed in ref. [35][36][37].…”
Section: Dynamic Rna Structures In the Dengue Virus Genomementioning
confidence: 99%
“…The concept of "one RNA, one function" (e.g., for tRNA or mRNA) is increasingly seen as far too simplistic with RNAs known to alter their secondary/tertiary structures in regulated ways to control the appearance of distinct functional states (1). This multifunctionality is also true of the genomes of singlestranded (ss) RNA viruses, where refolding to promote replication, translation and control of gene expression are well known (2). Here we describe additional layers of previously unsuspected functions within the genome of the satellite plant virus, Satellite Tobacco Necrosis Virus (STNV).…”
mentioning
confidence: 99%
“…These structures regulate many stages of the viral replication cycle, including genome replication, genome packaging into new viral particles, and intracellular trafficking (5,6,30,36,42). Studies on recombination in RNA viruses in general and in retroviruses in particular have indicated that RNA secondary structures play a potentially important role in genetic recombination (8,9,12,13,16,21,23,24,41).…”
mentioning
confidence: 99%